58. Validation of some alliances of the Aegean chasmophytic vegetation of the Asplenietea trichomanis - Bergmeier, Erwin; Dimopoulos, Panayotis; Mucina, Ladislav (Lazaroa, 2011)
We validated the alliances Asterion cretici, Capparo-Amaracion, Inulion heterolepidis and Petromarulo-Centaurion argenteae, all classified within the Cirsietalia chamaepeuces (Asplenietea trichomanis) -an order of the thermo- and mesomediterranean chasmophyte-rich vegetation of calcareous cliffs of the Aegean region (Hellas and possibly also western Turkey). The name of the Polygonion icarici, an alliance having currently uncertain position within the Asplenietea trichomanis), was also validated. The nomenclatural history of the Cirsietalia chamaepeuces, and its relationship to the Petromaruletalia pinnatae, have been clarified.